2000
DOI: 10.1111/j.1346-8138.2000.tb02285.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐ulcerative Basal Cell Carcinoma

Abstract: We report two cases of basal cell carcinoma (BCC) arising on the genitalia. The first case was a 49-year-old male who became aware of a dull erythematous plaque with a keratotic surface on his scrotal skin, and the second case was a 44-year-old female suffering from a keratotic plaque on her right vulvar region. Neither lesion was ulcerative. Both were resected under local anesthesia following a clinical diagnosis of angiokeratoma for the former and seborrheic keratosis or BCC for the latter lesion. Histopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Genital BCCs tend to develop in an older age group, with similar mean age at presentation for women (mean 71 years) and men (mean 69.9 years) in this cohort. Male sex is one risk factor for BCC outside the genitalia, while genital BCCs are predominantly reported in females in previous literature (16,17). Similarly, in this study, the majority of patients with genital E-H).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Genital BCCs tend to develop in an older age group, with similar mean age at presentation for women (mean 71 years) and men (mean 69.9 years) in this cohort. Male sex is one risk factor for BCC outside the genitalia, while genital BCCs are predominantly reported in females in previous literature (16,17). Similarly, in this study, the majority of patients with genital E-H).…”
Section: Discussionsupporting
confidence: 66%
“…The reason for this female predominance remains to be clarified. One possible explanation is the presence of a chronic skin irritation such as chronic vulvovaginitis, since most patients with vulvar BCC tend to be postmenopausal with drastically reduced hormone levels (16). Despite the higher incidence, females had better DSS than males, and the cause remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Other etiologic factors must be considered when BCC appears in sun‐protected skin such as the perianal and genital regions. Previous studies suggested that BCC in the perianal or genital regions may be a result of nonspecific factors such as generalized depression of immunosurveillance due to old age, poor hygiene, local chronic skin irritation, previous radiotherapy, and exposure to arsenic and other toxic substances . In this study, all 10 cases of BCC occurred in elderly patients (median age 70) with no history of previous radiation or exposure to toxic substances.…”
Section: Discussionmentioning
confidence: 99%
“…In most case reports, lesion size, specific anatomic site, patient age, treatment, recurrence, associated metastases, and provider specialty were available. These data were noted and tabulated yielding 96 reports in the English literature describing 437 patients with BCCs of the vulva . Of the 96 reports, 41 were published in the gynecology or gynecologic oncology literature, 29 in the dermatology literature, and 26 in nongynecology, nondermatology literature (pathology, surgery, oncology, medicine).…”
Section: Literature Review: Materials and Methodsmentioning
confidence: 99%